Step-Up Approach for Sodium Butyrate Treatment in Children With Congenital Chloride Diarrhea - Di Meglio, Lavinia; Grimaldi, Giusi; Esposito, Francesco; Gelzo, Monica; Esposito, Maria Valeria; Castaldo, Giuseppe; Canani, Roberto Berni (Frontiers in Pediatrics, 2022)
Abstract Objectives. Oral salt substitutive therapy is pivotal for the survival of patients with congenital chloride diarrhea (CLD), however this therapy is unable to influence the symptoms severity. Butyrate has been proposed to limit diarrhea severity in CLD. Unfortunately, the optimal dose schedule is still largely undefined. In addition, butyrate seems not to be well tolerated by all pa-tients, with some subjects reporting diarrhea worsening. We investigated the efficacy of a step-up therapeutic approach with sodium butyrate in patients who experienced a diarrhea worsening or an absent improvement after the direct administration of 100 mg/kg/day of sodium butyrate. Methods. The efficacy of a step-up therapeutic approach starting from 50 mg/Kg/day with a subsequent 25 mg/kg/day weekly increase up to 100 mg/kg/day of oral sodium butyrate was in-vestigated. in previously three unresponsive CLD children. Results. The step-up therapeutic approach resulted effective in limiting diarrhea severity in all our three previously unresponsive CLD patients. Conclusions. Our results suggest the efficacy of the step-up therapeutic approach in CLD children.